Effect of Intraoperative Midazolam on Postoperative Delirium in Older Surgical Patients: A Prospective, Multicenter Cohort Study - Li, Hao; Liu, Chang; Yang, Yu; Wu, Qing-Ping; Xu, Jun-Mei; Wang, Di-Fen; Sun, Jing-Jia; Mao, Meng-Meng; Lou, Jing-Sheng; Liu, Yan-Hong; Cao, Jiang-Bei; Duan, Chong-Yang; et al. (Anesthesiology (Philadelphia), 2025)
Midazolam is a short-acting benzodiazepine frequently used in the perioperative setting. This study aimed to investigate the potential impact of intraoperative midazolam on postoperative delirium in older patients undergoing noncardiac surgery. This study included patients aged 65 yr and older who received general anesthesia between April 2020 and April 2022 in multiple hospitals across China. Postoperative delirium occurring within 7 days was assessed using the 3-min Diagnostic Interview for Confusion Assessment Method. Univariable and multivariable logistic regression models based on the random effects were used to determine the association between midazolam administration and the occurrence of postoperative delirium, presented as the risk ratio and 95% CI. A Kaplan-Meier cumulative incidence curve was plotted to compare the distribution of time to postoperative delirium onset between patients who received midazolam and those who did not. Subgroup analyses based on specific populations were performed to explore the relationship between midazolam and postoperative delirium. In all, 5,663 patients were included, of whom 723 (12.8%) developed postoperative delirium. Univariate and multivariable logistic regression analyses based on random effects of different hospitals showed no significant association between midazolam medication and postoperative delirium among older population (unadjusted risk ratio, 0.96; 95% CI, 0.90 to 1.30; P = 0.38; and adjusted risk ratio, 1.09; 95% CI, 0.91 to 1.33; P = 0.35). The Kaplan-Meier curve showed no difference in the distribution of time to postoperative delirium onset (hazard ratio, 1.02; 95% CI, 0.88 to 1.18; P = 0.82). The results of subgroup analyses found that intraoperative midazolam treatment was not associated with postoperative delirium in the specific subgroups of patients. Intraoperative administration of midazolam may not be associated with an increased risk of postoperative delirium in older patients undergoing noncardiac surgery.